2018
DOI: 10.1097/mpg.0000000000001843
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Parenchymal Injury in Crigler‐Najjar Type I

Abstract: For the first time, we report a 41% prevalence of clinically silent, yet histologically significant fibrosis among subjects with Crigler-Najjar type 1. Risk for fibrosis appears to accrue with time, indicating that earlier intervention may be prudent whenever considering alternative treatments such as hepatocyte transplant, auxiliary liver transplant, or viral gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(54 reference statements)
0
19
1
Order By: Relevance
“…Liver fibrosis appears to develop in a proportion of CNS‐I patients over time, as suggested by Mitchell et al, who found pericentral, periportal, and mixed patterns of fibrosis in nine (41%) of 22 CNS‐I explants at the time of transplant and noted that patients with fibrosis were older (16.1 years) than those without (10.5 years; P = 0.02).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Liver fibrosis appears to develop in a proportion of CNS‐I patients over time, as suggested by Mitchell et al, who found pericentral, periportal, and mixed patterns of fibrosis in nine (41%) of 22 CNS‐I explants at the time of transplant and noted that patients with fibrosis were older (16.1 years) than those without (10.5 years; P = 0.02).…”
Section: Resultsmentioning
confidence: 63%
“…Of these, three were general review articles, one of which also included results of an international survey . Of the remaining 25 publications, eight were case series or case reports, 10 were retrospective cohorts, three were prospective cohorts, two were RCTs, and two were cross‐sectional studies . Nineteen primary publications were specific to CNS, while six comprised patients with various inherited metabolic disorders including CNS .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial intelligence programs have been used widely to prevent the ordering of related tests in the analytical phase. AST is one such test, which is commonly used to screen for liver diseases; its levels increase correspondingly with ALT levels [8,9]. There are only a very few conditions under which ALT is found to be within normal ranges and where AST is elevated above the normal limits, hemolysis being the most common of those [10].…”
mentioning
confidence: 99%